High levels of oxidative stress in rats infected with Blastocystis hominis - Chandramathi, S.; Suresh, K.; Shuba, S.; Mahmood, A.; Kuppusamy, U.R. (2010)
Objective: Numerous studies have revealed the presence of oxidative stress in parasitic infections. However, such studies were lacking in the Malaysian population. Previously, we have provided evidence that oxidative stress is elevated in Malaysians infected with intestinal parasites. Stool examinations revealed that about 47.5 of them were infected with the polymorphic protozoa, Blastocystis hominis. However, they were found to have mixed infection with other intestinal parasites. Methodology: Therefore, in order to investigate the role of B. hominis alone in affecting oxidative stress status, here we compared the levels of oxidative stress biomarkers in urine and blood samples between uninfected and B. hominis-infected rats. Results: Infected rats exhibited elevated levels of oxidative indices namely advanced oxidative protein products (AOPP), hydrogen peroxide (H(2)O(2)) and lipid hydroperoxide indicating that their overall oxidative damage level was higher. Ferric reducing antioxidant power (FRAP) was elevated at the initial stage of infection but decreased significantly during the last week of study duration suggesting that the antioxidant status of the host may be overwhelmed by oxidative damage. Conclusion: To date, this is the first comprehensive in vivo study to provide evidence for Blastocystis infection to correlate with significant oxidative burst leading to oxidative stress.